Case of thyroid transcription factor-1-positive neuroendocrine carcinoma of the sphenoid sinus with bone metastases - Kohei Inomata; Hidenori Yokoi; Masachika Fujiwara; Yasuaki Kimura; Yuma Matsumoto; Shoji Naito; Arisa Ohara; Naohiro Okano; Hiroshi Kamma; Koichiro Saito (Elsevier, 2021)
Malignant tumors in the sinonasal region are rare and account for only 0.2-0.8% of all cancers and 1-3% of all head and neck carcinomas. Among the confirmed cases, the involvement of the sphenoid sinus is even rarer, accounting for only 2-3% of paranasal sinus tumors (Osguthorpe et al., 1994; Esposito et al., 2006; DeMonte et al., 2000).Neuroendocrine carcinoma of the sphenoid sinus as a primary lesion is very rare; due to its rarity, no standard treatment has been established. Staining for thyroid transcription factor-1 (TTF-1) has been shown to be useful in the definite diagnosis of primary lung tumors. However, cases of TTF-1-positive small-cell neuroendocrine carcinomas that did not originate in the lung have been reported in the literature. Herein, we report the case of a patient with TTF-1-positive small-cell neuroendocrine carcinoma of the sphenoid sinus as the primary lesion and multiple bone metastases; to the best of our knowledge, this is the first report of such a case. A 52-year-old woman presented with complains of numbness and pain that extended from the left cheek to the lower lip and continued for 2 months. Head magnetic resonance imaging showed a neoplastic lesion in the left sphenoid sinus. We performed a transnasal endoscopic tumor biopsy; based on the results of pathological and immunohistochemical examination, a diagnosis of TTF-1-positive neuroendocrine carcinoma of the left sphenoid sinus with multiple bone metastases was made. Despite treatment with Cyberknife therapy and chemotherapy, the patient died approximately 12 months after treatment initiation. The findings of this case may help elucidate the significance of TTF-1-positive cells in small-cell neuroendocrine carcinomas.